An algebra problem by A Former Brilliant Member

Algebra Level pending

If ( m + 2 ) ( m 2 4 ) = ( m + 2 ) q ( m 2 ) (m+2) (m^2-4)=(m+2)^q (m-2) for all values of m m , what is the value of q q ?


The answer is 2.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Factor the left side.

( m + 2 ) ( m + 2 ) ( m 2 ) = ( m + 2 ) q ( m 2 ) (m+2) (m+2) (m-2) = (m+2)^q (m-2)

( m + 2 ) 2 = ( m + 2 ) q (m+2)^2 = (m+2)^q

2 = q 2 = q

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...